Development of sustainable tourism driven by policies, consumer trends, and environmental challenges in Poland and Serbia - Pomianek, Iwona; Kljajić, Nataša (Acta Scientiarum Polonorum. Oeconomia, 2025)
Aim: The article aims to compare the approaches to sustainable tourism in Poland and Serbia. It analyzes current consumer trends in the European Union, Poland (as an EU member), and Serbia (as an EU candidate country). The article presents the objectives of both countries’ latest available tourism development strategies. An attempt is made to indicate the desired directions of action in the near future from the perspective of changing expectations of tourists, environmental challenges, and the assumptions of the sustainable development concept. Methods: The methods included desk research (analysis of documents and public policies), content analysis (analysis of the websites of national tourism development agencies), and case studies (indicating specific actions). Results: The analysis of sustainable tourism development in Poland and Serbia indicates significant similarities, but also differences resulting from the political and institutional context. As an EU member, Poland systematically implements the recommendations resulting from a set of political initiatives under the common name of the European Green Deal and the industrial strategy published as the Transformation Path for Tourism, emphasizing the development of low-emission, digital tourism and supporting local communities. In the process of integration with the EU, Serbia is taking actions similar to EU standards, developing tourism based on natural values and cultural heritage. Conclusions: Both in Poland and Serbia, there is a growing interest in sustainable tourism among consumers and changing trends in the expectations of tourists. Environmental challenges, such as excessive pressure from mass tourism, loss of biodiversity, waste generation, and the effects of climate change, require an integrated approach and intersectoral cooperation; in this context, the assumptions of the circular economy are also relevant. This is necessary to balance economic development and the protection of natural resources. Poland and Serbia have significant potential for developing sustainable tourism but face different challenges. Poland should focus on reducing overtourism and better managing tourist traffic, while Serbia should invest in tourist infrastructure and environmental protection. Supporting innovation and ecological education for tourists and local communities is crucial.